Β-Diversity of morphological groups as indicator of coralligenous community quality status. (February 2020) - Appolloni, L.; Ferrigno, F.; Russo, G.F.; Sandulli, R.
Highlights: Coralligenous (C) assemblages are affected by environmental impact factors. Morphological Groups (MGs) are very helpful proxies when using indirect sampling techniques. C quality status was evaluated by Coralligenous Bioconstructions Quality Index (CBQI) MGs and CBQI are related to β-diversity. High β-diversity was recorded in the low C quality sites. Abstract: Sciaphilous organisms compose the Mediterranean coralligenous assemblages which have solar irradiance reduction in the water column as a main structuring environmental factor. These communities and associated habitats are taken into consideration for protection at European level, and monitoring activities of their status are mandatory (Marine Strategy Framework Directive, 2008/56/EC) representing hot spots of biodiversity. However, sampling activities of these habitats are often very expensive, thus, in recent years, remote surveys performed by underwater robots (ROVs) are more and more applied. In the present investigation Morphological Groups (MGs), which are parataxonomic proxies allowing to describe coralligenous assemblages using ROV images, are used to assess community structure and diversity of six randomly chosen sites in the Gulf of Naples, as representative of three substrate types (boulders/debris, rocky cliff and sand/mud) at two depths (De < 60 m and 60 m < De < 90 m). Results are also related to specific values of a previously developed index, Coralligenous Biocostructions Quality Index (CBQI), in order to evaluate if their β-diversity, measured as small-scale heterogeneity (differences among replicates), might represent a good indicator of assemblages quality status. Results show that the most abundant MGs in all substrates and depths are represented by crustose coralline algae and encrusting sponges, which account for significant quantitative differences only among sites ( p  < 0.001), but not among the substrate and among the depth factors ( p  = 0.5246). On the contrary, significant differences in β-diversity among substrates and depths are detected ( p =  0.004), highlighting a peculiar result: more heterogeneous assemblages are associated to low CBQI values. Such findings suggest that, i) similar coralligenous assemblages structures are strictly related to edaphic factors; ii) the apparent contradiction between high CBQI values and low heterogeneities might be explained by the long successional process of bioconstruction formation, converging in similar assemblages coherently with substrate and depth-related factors. Thus, to this respect, a low small-scale heterogeneity of assemblages (as a proxy of β-diversity measure) may be considered as a reliable indicator of high quality status.